Progressive islam's efforts to build ecological justice in Indonesia: A constitutional jihad approach and legal advocacy with muhammadiyah - Peggy Dian Septi Nur Angraini; Nur Halimah Widowati; Arya Diandra Diranova Ryanshah (Institute Of computer Science (IOCS), 2026)
Ecological degradation and inewuitable natural resource governance in Indonesia reveal a significant gap between constitutional guarantees of the right to a healthy environment and the implementation of public policies. Prevous studies have generally examined Muhammadiyah’s constitutional jihad and legal advocacy separately, leaving the relationship between these two approaches as a strategy of Progressive Islam for achieving ecological justice insufficiently explored. This study aims to analyse the concept and practice of Muhammadiyah’s constitutional jihad and the role of legal advocacy jihad in addressing legal injustice and public policy issues. The novelty of this research lies in proposing an integrated framework that combines constitutional jihad as a structural legal reform strategy with legal advocacy jihad as a community based mechanism for protecting public rights. This qualitative study employs research approach by analysing academic literature, legal documents, judicial review decisions, and official Muhammadiyah publications. The findings demonstrate that constitutional jihad and legal advocacy jihad complement one another through constitutional litigation, policy advocacy, community empowerment, and public participation to promote ecological justice. This study contributes to the development of Islamic legal studies and constitutionalism law by offering an integratve model of transformative da’wah that strengthens constitutionalism, environmental protection, and social justice in Indonesia.